HIERARCHICAL AND STRUCTURAL COMPONENTS OF LINGUO-METHODICAL THINKING - Pardayeva Diyora Tokhirovna (Bright Mind Publishing, 2025)
The development of linguo-methodical thinking is essential for the effective professional formation of a modern foreign language teacher. This type of thinking integrates linguistic knowledge with methodological awareness and reflective pedagogical reasoning. The present article explores the hierarchical and structural components of linguo-methodical thinking, aiming to clarify its internal organization and functional elements. The research identifies key levels of development-ranging from reproductive application of teaching methods to creative and adaptive use of linguistic and didactic tools in diverse classroom contexts.
Keywords: Linguo-methodical thinking; teacher cognition; methodological competence; structural components; levels of thinking; language pedagogy; foreign language teacher education; reflective practice; instructional design.